2014
DOI: 10.5194/amt-7-941-2014
|View full text |Cite
|
Sign up to set email alerts
|

Vertical profile of δ<sup>18</sup>OOO from the middle stratosphere to lower mesosphere from SMILES spectra

Abstract: Abstract.Ozone is known to have large oxygen isotopic enrichments of about 10 % in the middle stratosphere; however, there have been no reports of ozone isotopic enrichments above the middle stratosphere. We derived an enrichment δ 18 OOO in the stratosphere and the lower mesosphere from observations of the Superconducting SubmillimeterWave Limb-Emission Sounder (SMILES) onboard the International Space Station (ISS) using a retrieval algorithm optimized for the isotopic ratio. The retrieval algorithm includes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 62%
“…As is the case for total 50 O 3 in the tropical and northern latitude bands, discussed above, the MIPAS global mean δ(a− 50 O 3 ) shows a decrease above 33 km; other datasets also show a decrease with altitude, starting at 40 km for the FTIR dataset of Haverd et al (2005) and the SMILES dataset of Sato et al (2014), or at 30 km for the FIRS-2 dataset of Johnson et al (2000). The ATMOS dataset of Irion et al (1996) shows a steady increase up until the maximum retrieval altitude of 40 km.…”
Section: Globalmentioning
confidence: 96%
See 3 more Smart Citations